Design principles of ocular drug delivery systems: importance of drug payload, release rate, and material properties - Subrizi, Astrid; del Amo, Eva M.; Korzhikov-Vlakh, Viktor; Tennikova, Tatiana; Ruponen, Marika; Urtti, Arto (Drug discovery today, 2019)
•Ocular drug delivery is a field in which regular ADME tools are not useful.•Pharmacokinetics based dosing aid for ocular drug delivery is presented.•User-friendly dosing aid guides early stage design of delivery systems.•Guidance for the delivery route, dosing and formulation design is presented. Ocular drugs are usually delivered locally to the eye. Required drug loading, release rate, and ocular retention time of drug delivery systems depend on the potency, bioavailability, and clearance of the drug at the target site. Drug-loading capacity of the formulation is limited by the material properties and size constraints of the eye. The design aid described herein for ocular drug delivery systems guides the calculation of steady-state drug concentrations in the ocular compartments, taking into account drug dose, bioavailability, and clearance. The dosing rate can be adjusted to reach the target drug concentrations, thereby guiding the design of drug delivery systems for topical, intravitreal, and subconjunctival administration. The simple design aid can be used at early stages of drug development by investigators without expertise in pharmacokinetic and pharmacodynamic modeling. Successful drug delivery to ocular targets depends on ocular biology, drug properties, and formulation characteristics. A multifactorial design aid for ocular drug delivery is presented.